A Novel Ant Colony Optimization Algorithm for Large Scale QoS-Based Service Selection Problem - Changsheng Zhang; Hao Yin; Bin Zhang (Discrete Dynamics in Nature and Society)
To tackle the large scale QoS-based service selection problem, a novel efficient clustering guided ant colony service selection algorithm called CASS is proposed in this paper. In this algorithm, a skyline query process is used to filter the candidates related to each service class, and a clustering based shrinking process is used to guide the ant to the search directions. We evaluate our approach experimentally using standard real datasets and synthetically generated datasets and compared it with the recently proposed related service selection algorithms. It reveals very encouraging results in terms of the quality of solution and the processing time required.